The effect of religious activities on the religious character of students at MA Sirnamiskin Bandung City - Morsal, Rahmi Aulia Em; Yakiin, Wulandari Fithriyah; Nurhayati, Anisa; Nurlaela, Ilma; Apriyansyah, Imam; Suhendi, Endi (Educenter : Jurnal Ilmiah Pendidikan, 2024)
The rapid development of modern science and technology in the era of globalisation has opened a new era in social development, culture, and the mindset of mankind. In its development process, this era has created various challenges that must be solved, especially in the world of education. One of the challenges experienced by the world of education in the global era is the decline in moral quality or the degradation of national identity. Therefore, there is a need for moral improvement and development through the cultivation of religious character values in students at school, with the implementation of religious activities. The purpose of this study is to determine how religious activities, the level of religious character of students, and the effect of religious activities on the religious character of students at MA Sirnamiskin Bandung City. The research method used is the survey method. The population in this study were all students of MA Sirnamiskin Bandung City, totalling 318 students. The sampling technique in this study is probability sampling using simple random sampling technique. So that 48 respondents were selected as the research sample. The results of this study indicate that first, religious activities at MA Sirnamiskin Bandung City are in the good category. Second, the level of religious character of students at MA Sirnamiskin Bandung City is in the good category. Third, there is a significant influence between religious activities on the religious character of students at MA Sirnamiskin Bandung City. It can be concluded that there is an influence of religious activities on the religious character of students. The more religious activities are carried out, the more the religious character of students will increase.